Physical activity of students - Macanović, Gordana (PONS - medicinski časopis, 2014)
Goal.Goal of this study is to examine how much students are involved in a physical activity in their free time. Methods . This study included 410 students of the first , second, third and fourth years . The research was designed as a cross sectional study , a sample is made at random , using a questionnaire with closed answers in different variants . Results.Od 410 students surveyed , 215 women (52.4 %) and 195 men (47.5 %). Physical activity is engaged in 270 ( 77.7 %) students , of whom 165 (56.8 %) men and 125 (43.1 %) women. Most of respondents 161 (55.5 %) , engaged in physical activity two to three times week , of which 100 of them (24.3 %) is only active for 30 minutes. Students most often go to the gym 68 ( 23.4 %). The surveyed students are sitting as often as 4 hour 160 ( 39%), and there are students who spend sitting more than 8 hours , 120 ( 29.2 %). Conclusion . Based on the research it can be concluded that involvement in sport and physical activity is not enough. Most of interviewed students has rare and very short physical activity. A large percentage of students spent a lot of time sitting in front of the computer and TV. Measures to promote a healthy lifestyle must have modern concept and to relate to the whole of society and family and to involve medical institutions and all institutions concerned with the education of young people. Keywords . students , lifestyle , sport, health